Glucolipid metabolism improvement in impaired glucose tolerance subjects consuming a Quinoa-based diet: a randomized parallel clinical trial - Zeng, Hongli; Cai, Xiangsheng; Qiu, Zhenyang; Liang, Yuchan; Huang, Lu (Frontiers in Physiology, 2023)
To investigate the effects of quinoa on glucose and lipid metabolism, and the prognosis in people with impaired glucose tolerance.Methods: One hundred and thirty-eight patients diagnosed with impaired glucose tolerance following a glucose tolerance test in Guangzhou Cadre Health Management Center were selected and randomly divided into quinoa intervention and control groups, according to the digital table method. After one year of follow-up, the differences in blood glucose, blood lipid, glycosylated hemoglobin and other indicators were compared. The disease prognosis between the two groups was also compared.The two hours postprandial blood glucose, glycosylated hemoglobin, insulin resistance index, total cholesterol, low-density lipoprotein cholesterol, body mass index, waist circumference, systolic and diastolic blood pressure after intervention in the quinoa group were significantly lower than before intervention. In contrast, high-density lipoprotein cholesterol was higher than before intervention and is statistically significant (P<0.05). After one year of follow-up, the control group's glycosylated hemoglobin and body mass index are higher than before intervention, and are statistically significant (P<0.05). The 2-hour postprandial blood glucose, glycosylated hemoglobin, insulin resistance index, body mass index, and mean diastolic blood pressure in the quinoa group are statistically significantly lower than in the control group, while high-density lipoprotein cholesterol is higher (P<0.05). The rate of conversion to diabetes for participants in the quinoa group (7.8%) is statistically significantly lower than in the control group (20.3%) (χ2=12.760, P=0.002). Logistic regression analysis showed that quinoa consumption is a protective factor for developing diabetes (P<0.05).Adding quinoa to staple food intake can reduce postprandial blood glucose, and improve lipid metabolism and insulin resistance, delaying the progression of diabetes in people with impaired glucose tolerance.